The Relationship between Communication Channels and Health Behavior - Febrina, Diah; Saleh, Amiruddin; Suhaeti, Rita Nur; Muljono, Pudji (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
The epidemiological transition has occurred significantly over the last two decades, with non-communicable diseases (NCDs) becoming the main burden. In context of health communication, health campaign activities are expected to reduce these problems. The objective of the research is to analyze health communication channels and the relationship between health communication channels and health behavior. Data were collected by applying a survey method using a self-administered questionnaire. The survey was conducted in Depok City, West Java, Indonesia. Respondents were residents of aged fifteen years and over, who had been exposed to health promotion campaigns or activities from the various communication channels used. Total sample size was 120 respondents. Univariate analysis was applied to get frequency distribution tables, while bivariate analysis was applied using Pearson correlation analysis. The research results indicate that majority of the residents are still in moderate category with regard to implementing health behaviors. There are still many people, who implement unhealthy behaviors, particularly with regard to regular health checks. Secondly, the frequency of use of health promotion communication channels remains low. New media channels, interpersonal media and community media are three channels that are perceived as trustworthy, attractive and credible. Thirdly, this study found that the frequency of using communication channels, channel trustworthiness, attractiveness and credibility have a significant relationship with health behavior. The findings of this study have implications for health campaign program designers, who should consider including campaign messages that can lead to improve public health behavior and prevent the occurrence of NCDs.